Case report: Microsurgical replantation of heel skin and subcutaneous tissue - Zhou, Jian; Chang, Shusen; Deng, Chengliang; Huang, Guangtao; Jin, Wenhu; Chen, Wei; Wei, Zairong (Frontiers in Surgery, 2023)
A 36-year-old healthy male patient was presented to the emergency room 3 h after experiencing a laceration to the left foot caused by a porcelain shard. The defect measured 7.5 × 6.0 × 0.8 cm, and the composite amputated tissue consisted of skin and subcutaneous layers. The terminal branch of the lateral calcaneal artery was first anastomosed end-to-end to the corresponding artery in the wound defect. The lateral calcaneal nerve was anastomosed after blood flow was restored. The two lateral veins were anastomosed end-to-end to the corresponding veins in the wound defect. Postoperatively, 1.0×1.5 cm area of skin necrosis was present at the distal end of the tissue, which healed smoothly after two weeks of dressing changes. The patient had retained excellent aesthetic and functionality by the 37-month follow up. Although such isolated amputation is relatively rare, microsurgical replantation is, thus, a feasible option in the management of heel amputation.